Evaluation of the phytochemical profile and uterine contractile effect of Woodfordia fruticosa (L.) Kurz and Dipsacus mitis D. Don - Gyawali, Rajendra; Jnawali, Deepak; Chang-Hun, Song; Kim, Kyong-Su (Journal of Nepal Pharmaceutical Association, 2012)
The phytochemical screening of Dipsacus mitis D. Don and Woodfordia fruticosa (L.) Kurz revealed the presence of bioactive secondary metabolites in both of the species but their concentrations were variable. Flavanoids and saponins were found in remarkable amount in both of the samples. The volatile compounds of both plants were extracted by Simultaneous Steam Distillation and Extraction (SDE) apparatus and analyzed by Gas Chromatography/Mass Spectrometery (GC-MS). Total 53 volatile compounds were tentatively identified from roots of Dipsacus mitis D. Don and 78 were identified from flowers of Woodfordia fruticosa (L.) Kurz. Alcohols were dominant in both the plants accounting 45% and 32% respectively. Numerous bioactive volatile compounds were detected in both herbs. The effects of increasing concentrations of the methanolic extracts on the amplitude and frequency of spontaneously contracting uterine tissues were tested. The effect of extracts on the smooth muscle strips from rat uterus showes the dramatic muscular relaxation on spontaneous contractility and was determided most effective at a concentration 6500 µg/ml of methanolic extract of Dipsacus mitis D. DOI: http://dx.doi.org/10.3126/jnpa.v26i1.6627 JNPA. XXVI(1) 2012 1-11